Fostering Digital Excellence: A Multidimensional Exploration of the Collective Effects of Technological Adaptability, Employee Competitiveness, and Employee Dynamic Capabilities on Employee Digital Performance in Chinese SMEs - Wang, Guifang; Mansor, Zuraina Dato; Leong, Yee Choy (International Journal of Social Science Research, 2024)
This study is grounded in a specific Eastern cultural region, undertaking a multidimensional exploration. We meticulously examined the intricate interplay between employee competitive attitudes (ECA) and behaviors (ECB), employee dynamic capability (EDC), and Competitive climate (CC), converging these factors to redefine the contours of Employee Digital Performance (EDP). The survey data for this study were collected from SMEs in four Chinese provinces: Shanghai, Guizhou, Guangdong, and Anhui. The analysis was conducted utilizing CB-SEM (AMOS) to analyze the newly conceptualized framework. The research findings unveil a profound reality: in the digital era, Technological Adaptability (TA), Employee Competitive Attitudes, Employee Competitive Behaviors, and Employee Dynamic Capabilities all exert positive influences on Employee Digital Performance. The study indicates that technological adaptability, as a forward variable of employee competitive attitude and employee competitive behavior, positively influences employees' competitive attitudes and behaviors. Employees possessing competitive attitudes and behaviors enhance their dynamic capabilities, thereby promoting employee digital performance. Furthermore, the research indicates that the Competitive Climate moderates Employee Competitive Behaviors, and Employee Competitive Attitudes drive Employee Dynamic Capabilities, enhancing Employee Digital Performance. In the process of Chinese SMEs striving for digital advantages, this research provides a distinctive perspective. It offers actionable insights into harnessing employees’ traits and capabilities within the continually evolving digital ecosystem.